Innovate therapeutic targets for autoimmune diseases: insights from proteome-wide mendelian randomization and Bayesian colocalization - Qiubai Jin; Feihong Ren; Ping Song (Taylor & Francis Group, 2024)
AbstractBackground Despite growing knowledge regarding the pathogenesis of autoimmune diseases (ADs) onset, the current treatment remains unsatisfactory. This study aimed to identify innovative therapeutic targets for ADs through various analytical approaches.Research design and methods Utilizing Mendelian randomization, Bayesian co-localization, phenotype scanning, and protein-protein interaction network, we explored potential therapeutic targets for 14 ADs and externally validated our preliminary findings.Results This study identified 12 circulating proteins as potential therapeutic targets for six ADs. Specifically, IL12B was judged to be a risk factor for ankylosing spondylitis (p = 1.61E − 07). TYMP (p = 6.28E − 06) was identified as a protective factor for ulcerative colitis. For Crohn's disease, ERAP2 (p = 4.47E − 14), HP (p = 2.08E − 05), and RSPO3 (p = 6.52E − 07), were identified as facilitators, whereas FLRT3 (p = 3.42E − 07) had a protective effect. In rheumatoid arthritis, SWAP70 (p = 3.26E − 10), SIGLEC6 (p = 2.47E − 05), ISG15 (p = 3.69E − 05), and FCRL3 (p = 1.10E − 10) were identified as risk factors. B4GALT1 (p = 6.59E − 05) was associated with a lower risk of Type 1 diabetes (T1D). Interestingly, CTSH was identified as a protective factor for narcolepsy (p = 1.58E − 09) but a risk factor for T1D (p = 7.36E − 11), respectively. External validation supported the associations of eight of these proteins with three ADs.Conclusions Our integrated study identified 12 potential therapeutic targets for ADs and provided novel insights into future drug development for ADs.